Combination treatment with fingolimod and a pathogenic antigen prevents relapse of glucose‐6‐phosphate isomerase peptide‐induced arthritis. Issue 3 (8th June 2016) - Yoshida, Yuya; Mikami, Norihisa; Matsushima, Yuki; Miyawaki, Mai; Endo, Hiroki; Banno, Rie; Tsuji, Takumi; Fujita, Tetsuro; Kohno, Takeyuki
Abstract : Introduction: Combination treatment with fingolimod (FTY720) plus pathogenic antigen is thought to prevent glucose‐6‐phosphate isomerase (GPI)325‐339 ‐induced arthritis progression by effective induction of immune tolerance. Here, we examined the efficacy of this combination treatment on remission maintenance. Methods: GPI325‐339 ‐induced arthritis mice were treated for 5 days with FTY720 (1.0 mg/kg, p.o .) alone, GPI325–339 (10 μg/mouse, i.v .) alone, or with the FTY720 plus GPI325‐339 combination. In some experiments, mice were resensitized with GPI325‐339 . Results: Following resensitization with GPI325‐339, combination‐treated mice exhibited neither severe relapse nor elevated lymphocyte infiltration in joints. Neither anti‐human nor mouse GPI325‐339 antibody levels were correlated with clinical symptoms. This suggests that combination treatment prevents relapse following resensitization via regulation of pathogenic antigen‐specific T cells. The proportion of regulatory T (Treg) cells in inguinal lymph nodes was increased post treatment in the FTY720 alone and FTY720 plus GPI325‐339 groups. In contrast, the proportion of glucocorticoid‐induced tumor necrosis factor receptor‐family‐related gene/protein (GITR) + non‐Treg cells was increased only in combination‐treated mice. Furthermore, GITR + non‐Treg cells, which were induced by the combination treatment in vivo, possess suppressive activity and high ability to produce interleukin (IL)‐10. Conclusion: GITR + non‐Treg cells might play a key role in relapse prevention following resensitization. Thus, this combination treatment might establish immune tolerance by induction of GITR + non‐Treg cells. Abstract : In this study, we demonstrated that the combination treatment with fingolimod (FTY720) plus pathogenic antigen (glucose‐6‐phosphate isomerase (GPI)325‐339 ) could induce and maintain remission of GPI325‐339 ‐induced arthritis. GITR + CD25 − CD4 + cells, which constitute the anergic population, might prevent relapse following resensitization via high level production of IL‐10; the GITR + non‐Treg cells that were induced by the combination treatment might play a key role in the establishment of tolerance.